EDUCATION AND PUBLIC SECURITY: A BRIEF ESSAY ON THE TRAINING OF MILITARY POLICE OFFICERS FOR POLICE APPROACHES AND THE RACIAL ISSUE - Castiajo, Daniel (Revista Gênero e Interdisciplinaridade, 2026)
This course completion paper proposes a reflection on the challenge of the educator's role as a mediator of knowledge in the training of military police officers regarding racial issues. It deals, therefore, with the continuing education of military police officers working in the Baixada Fluminense, a peripheral area of ​​Rio de Janeiro. It is an extension of ongoing doctoral research in Education, Culture and Communication. An interdisciplinary approach is adopted, articulating bibliographic research with the production of qualitative data derived from observational participation in the exercise of teaching functions in Public Security. The study aims to examine how the concepts of structural and institutional racism can be addressed in order to reframe conceptions and ideas stemming from common sense among military police officers working in peripheral areas of Rio de Janeiro. The theoretical framework is based on authors such as Paulo Freire, Abdias do Nascimento, Lélia Gonzales, Michel Foucault, Jacqueline Muniz, and Elizabete Albernaz, allowing for the analysis of prejudice present in the discourse of these agents in training, as well as presenting accounts of actions that can be adopted as strategies for the professional improvement of military police officers in serving vulnerable groups. Preliminary results indicate that a considerable portion of military police officers, in most classes, demonstrate resistance to the topic, reproducing the discourse that legitimizes the approach of people with characteristics defined as suspicious and even a "standard color element." Such positions reinforce a "structural racism" and the reproduction of the "warrior ethos" that transcends time and remains contemporary, manifesting itself in daily police work, making the educator's task challenging in terms of knowledge production, in favor of promoting human rights.